The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/s22093350
|View full text |Cite
|
Sign up to set email alerts
|

New Results for the Error Rate Performance of LoRa Systems over Fading Channels

Abstract: Long Range (LoRa) systems have recently attracted significant attention within the research community as well as for commercial use due to their ability to transmit data over long distances at a relatively low energy cost. In this study, new results for the bit error rate performance of Long Range (LoRa) systems operating in the presence of Rayleigh, Rice, Nakagami-m, Hoyt, η-μ and generalized fading channels are presented. Specifically, we propose novel exact single integral expressions as well as simple, acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…For instance, LPWAN (low-power wide area network) INGENU technologies often use power allocation to extend battery life [40]. Conversely, LoRa typically employs rate control strategies coupled with fixed transmission power levels [41,42].…”
Section: Maximisation Of Effective Energy Efficiency With Qos Guaranteesmentioning
confidence: 99%
“…For instance, LPWAN (low-power wide area network) INGENU technologies often use power allocation to extend battery life [40]. Conversely, LoRa typically employs rate control strategies coupled with fixed transmission power levels [41,42].…”
Section: Maximisation Of Effective Energy Efficiency With Qos Guaranteesmentioning
confidence: 99%
“…In [ 7 , 15 ], the authors presented a relay node selection approach as a part of a system encompassing the optimization of resource allocation for the spreading factor, aiming to ensure maximum performance in terms of throughput, network coverage probability, and BER. The error rate performance is a relevant aspect for LoRa; thus, the authors of [ 16 ] presented new results for the BER performance of LoRa systems operating over various types of fading channels. Th simulation and numerical results in [ 7 , 15 ] demonstrated that such a system can improve BER and coverage probability for a given geographic area, but reduces throughput compared to the traditional LoRa system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The studies, [ 6 , 7 ] investigate the impact of Rayleigh fading on the BER of LoRa transmissions. These studies provide insights into LoRa’s performance under challenging channel conditions without exploring specific error correction or detection techniques employed within the LoRaWAN protocol itself.…”
Section: Introductionmentioning
confidence: 99%